Recovery of Native Brook Trout Populations Following the Eradication of Nonnative Rainbow Trout in Southern Appalachian Mountains Streams. (1st November 2016) - Kanno, Yoichiro; Kulp, Matt A.; Moore, Stephen E.
Abstract: Nonnative Rainbow Trout Oncorhynchus mykiss have displaced native Brook Trout Salvelinus fontinalis in many southern Appalachian Mountains streams. We monitored the population recovery of Brook Trout following Rainbow Trout eradication at 10 sites in seven allopatric Rainbow Trout streams located in Great Smoky Mountains National Park, USA. Rainbow Trout were successfully eradicated by electrofishing or Fintrol (also known as antimycin-A), and Brook Trout were reintroduced at low densities (39–156 fish/km) from streams located within the park. Within 2 years after reintroduction, the density and biomass of adult Brook Trout recovered to levels comparable to the prerestoration density and biomass of Rainbow Trout. Spawning in the first autumn after reintroduction was assumed by the presence of young-of-the-year fish in seven out of nine sites surveyed during the following summer. Brook Trout density and biomass 3–5 years after restoration did not significantly differ from those in natural allopatric populations within the park in young-of-the-year fish but were significantly lower in adults. Individual body size of adult and young-of-the-year fish were density dependent after restoration, indicating that Brook Trout populations had recovered to a point that habitat saturation triggered intraspecific competition. We conclude that Rainbow Trout removal has been a viable management technique to restore Brook Trout populations in the park. Received March 4, 2016; accepted July 17, 2016 Published online October 20, 2016